Estrategias pedagógicas en aulas hospitalarias - Choto Yucailla, Tamara Abigail (2025)
This study aimed to identify the pedagogical strategies used by teachers and the main difficulties encountered in the hospital classroom at the General Hospital of Puyo, and to propose diversified strategies aligned with the needs identified. The beneficiaries were teachers at different educational levels and hospitalized students, as the proposed strategies aim to enhance teaching and learning by offering new ways to instruct and adapt content to each student’s condition. A qualitative approach was applied to obtain a clearer understanding of the educational reality in the hospital environment. The research was basic and field-based, focused on expanding knowledge about pedagogical practices in hospital settings. The population consisted of five teachers, who also served as the sample due to its small size. Data were collected through a structured questionnaire with closed, multiple-choice questions, applied anonymously and voluntarily. In conclusion, the study enabled recognition of the educational dynamics, challenges, and the need to strengthen pedagogical strategies adapted to this specialized context